Tailored p‐Orbital Delocalization by Diatomic Pt‐Ce Induced Interlayer Spacing Engineering for Highly‐Efficient Ammonia Electrosynthesis. Issue 6 (13th December 2022) - Chen, Dong; Zhang, Shaoce; Yin, Di; Li, Wanpeng; Bu, Xiuming; Quan, Quan; Lai, Zhengxun; Wang, Wei; Meng, You; Liu, Chuntai; Yip, SenPo; Chen, Fu‐Rong; et al.
Abstract: Electrochemical nitrate reduction to ammonia (eNO3 RR) is a green and appealing method for ammonia synthesis, but is hindered by the multistep chemical reaction and competitive hydrogen generation. Herein, the synthesis of 2D SnS nanosheets with tailored interlayer spacing is reported, including both expansion and compression, through the active diatomic Pt‐Ce pairs. Taking together the experimental results, in situ Raman spectra, and DFT calculations, it is found that the compressed interlayer spacing can tune the electron density of localized p‐orbital in Sn into its delocalized states, thus enhancing the chemical affinity towards NO3 − and NO2 − but inhibiting hydrogen generation simultaneously. This phenomenon significantly facilitates the rate‐determining step (*NO3 →*NO2 ) in eNO3 RR, and realizes an excellent Faradaic efficiency (94.12%) and yield rate (0.3056 mmol cm −2 h −1 ) for NH3 at −0.5 V versus RHE. This work provides a powerful strategy for tailoring flexible interlayer spacing of 2D materials and opens a new avenue for constructing high‐performance catalysts for ammonia synthesis. Abstract : An interlayer spacing engineering of 2D SnS nanosheets is reported that involves adopting active diatomic Pt‐Ce, that tunes the electron density of localized p‐orbitals in Sn into its delocalized states, thus significantly improving NO3 − ‐to‐NH3 conversion for both activity and selectivity.